Sensing and communication based on novel laser technologies - Huang, Wei (2016)
Free-space optic (FSO) communication systems have been playing an important role in communication area, and the wave in range of Mid Infra Red (MIR) becomes advantaged as communication requires higher speed and longer distance. The fast developed technologies of MIR-QCLs promise a bright future of their wide application. However, currently available MIR-FSO systems are complicated and expensive, so they have a long way to go before getting popular. In this project a system based on a 4.7µm QCL was built, and the communication was demonstrated as reliable and effective with an analog audio. The devices controlling and data acquisition was realized by LabVIEW programming, and the laser was modulated by a pulse generator. The demo was made with a sound file lasting for 5 s, and the whole communication and processing procedure consumed 30 minutes to finish. According to the graphs of experiment results, waveform envelops were kept well during transmitting. In this phase there are two issues to be soleved for further work, namely the speed limited by current device and modulation method, and the noise derives from non-ideal performance of QCL.